FOREST STRUCTURE AND REGENERATION PATTERN OF BETULA UTILIS D. DON IN MANASLU CONSERVATION AREA, NEPAL - Sujakhu, Hishila; Gosai, Kamal Raj; Karmacharya, Siddhi Bir (Ecoprint: An International Journal of Ecology, 2014)
Forest structure and regeneration of Betula utilis (D. Don) was studied in birch forestlocated in Samagaun valley (3500 – 4000 m) of Manaslu Conservation Area. Vegetationsampling was done by quadrat method. Altogether 40 quadrats were sampled to determinethe Importance Value Index (IVI) of tree species, and distribution pattern of seedlings andsaplings. Regeneration was assessed by density - diameter curve. Four tree species wererecorded from the forest. Betula utilis was the dominant tree species with the highestImportance Value Index (173.22) in mixed Betula forest and 262.96 in pure Betula forestand Abies spectabilis was the co – dominant species (65.95) in mixed Betula forest whileRhododendron campanulatum was the co-dominant species (37.03) in pure Betula forest.Density of Betula utilis increased with increase in elevation where as density of other treespecies decreased with increase in elevation. Mixed Betula forest at lower elevation wasyoung. The density diameter curve of the tree population of Betula utilis, both on mixed andpure forests, deviated slightly from the typical reverse J shaped structure and hence did notshow the sustainable regeneration. The sapling density was higher than seedling density.The distribution of seedlings and saplings were not uniform among the sampling plots. DOI: http://dx.doi.org/10.3126/eco.v20i0.11472 ECOPRINT An International Journal of Ecology Vol. 20, 2013 page: 107-113